Erectogenic Effects of Clerodendron capitatum: Involvement of Phosphodiesterase Type-5 Inhibition - Abdelwahab, S.I.; Mohamed, A.H.; Oall, M.; Mohamed, O.Y.; Elhassan Taha, M.M.; Mohan, S.; Noordin, M.I.; Mustafa, Mohd Rais; M. Alkharfy, K. (Hindawi, 2011)
Clerodendron capitatum (Willd) (family: verbenaceae) is locally named as Gung and used traditionally to treat erectile dysfunction.Therefore, the current study was designed to investigate the erectogenic properties of C. capitatum. The relaxation eﬀect of this plant was tested on phenylephrine precontracted rabbit corpus cavernosum smooth muscle (CCSM). The eﬀects of C. capitatum were also examined on isolated Guinea pig atria alone, in the presence of calcium chloride (Ca 2+ channel blocker), atropine(cholinergic blocker), and glibenclamide (ATP-sensitive K +channel blocker). These eﬀects were conﬁrmed on isolated rabbit aortic strips. The extract, when tested colorimetrically for its inhibitory activities on phosphordiesterase-5 (PDE-5) in vitro towards pnitrophenyl phenyl phosphate (PNPPP), was observed to induce signiﬁcant dose-dependent inhibition of PDE-5, with an ID50 of 0.161 mg/ml (P < .05). In conclusion, our results suggest that C. capitatum possesses a relaxant eﬀect on CCSM, which is attributable to the inhibition of PDE-5, but not mediated by the release calcium, activation of adrenergic or cholinergic receptors, or the activation of potassium channels.